Exophytic benign mixed epithelial stromal tumour of the kidney: case report of a rare tumour entity - Richter, Michael (BioMed Central, 2010)
BACKGROUND: Mixed epithelial and stromal tumour (MEST) represents a recently described benign composite neoplasm of the kidney, which predominantly affects perimenopausal females. Most tumours are benign, although rare malignant cases have been observed. CASE REPORT: A 47-year-old postmenopausal female presented to the urologist with flank pain. A CT scan of the abdomen showed a 30-mm-in-diameter uniform mass adjacent to the pelvis of the left kidney. Surgical exploration showed a tumour arising from the lower anterior hilus of the left kidney. The tumour could be excised by preserving the kidney. By intraoperative frozen section the tumour showed characteristic features of MEST with epithelial-covered cysts embedded in an "ovarian-like" stroma. Additional immunohistochemistry investigations showed expression for hormone receptors by the stromal component of the tumour. DISCUSSION: MEST typically presents in perimenopausal women as a primarily cystic mass. Commonly, the tumour arises from the renal parenchyma or pelvis. The tumour is composed of an admixture of cystic and sometimes more solid areas. The stromal cells typically demonstrate an ovarian-type stroma showing expression for the estrogen and progesterone receptors. CONCLUSION: MEST represents a distinctive benign tumour entity of the kidney, which affects perimenopausal woman. The tumour should be distinguished from other cystic renal neoplasms. By imaging studies it is difficult to distinguish between a benign or malignant nature of the tumour. Thus, intraoperative frozen section is necessary for conservative surgery, since the overall prognosis is favourable and renal function can be preserved in most cases.